Analisis Determinan Pengungkapan Emisi Karbon (Studi Perbandingan Perusahaan di Indonesia dan Malaysia Periode 2013-2018) - Nur Arifah; Slamet Haryono (At-Taradhi Jurnal Studi Ekonomi, 2021)
This study aimed to examine the effects of the Global Reporting Initiative (GRI), The Reputation of Public Accounting Firms (KAP), environmental committees, leverage, environmental management systems and board size on carbon emission disclosure. The population of this study were the registered companies on The List of Sharia Securities in Indonesia and Malaysia, while the sample of this study was selected by using the purposive sampling method. The data in this study used panel data from 2013-2018. The study used SPSS Version 25 with the data analysis technique used multiple linear regression test and independent sample t test. The result showed that the variable Global Reporting Initiative (GRI), The Reputation of Public Accounting Firms (KAP) and environmental management systems have significant positive effects on carbon emission disclosure in Indonesia and Malaysia. The environmental committee variable has a significant positive effect on carbon emission disclosure in Indonesia, but has no effect in Malaysia. The leverage variable has a significant negative effect on carbon emission disclosure in Indonesia, but has no effect in Malaysia. The board size variable has a significant positive effect on carbon emission disclosure in Malaysia, but it has no effect in Indonesia and also there is a significant difference between the quality of carbon emission disclosure both in Indonesia and in Malaysia. Penelitian ini bertujuan menguji pengaruh Global Reporting Initiative (GRI), reputasi kantor akuntan publik (KAP), environmental committee, leverage, environmental management system dan board size terhadap carbon emission disclosure. Populasi dalam penelitian ini adalah perusahaan yang terdaftar dalam Daftar Efek Syariah Indonesia dan Malaysia, sedangkan sampel penelitian ini dipilih menggunakan metode purposive sampling. Data dalam penelitian ini menggunakan data panel dari tahun 2013-2018. Penelitian ini menggunakan SPSS Versi 25 dengan teknik analisis data menggunakan uji regresi linier berganda dan independent sample t test. Hasil penelitian menunjukkan bahwa variabel  Global Reporting Initiative (GRI), reputasi kantor akuntan publik (KAP) dan environmental management system berpengaruh positif signifikan terhadap carbon emission disclosure di Indonesia dan Malaysia. Variabel environmental committee berpengaruh posistif signifikan terhadap carbon emission disclosure di Indonesia, namun tidak berpengaruh di Malaysia. Variabel leverage berpengaruh negatif signifikan terhadap carbon emission disclosure di Indonesia, namun tidak berpengaruh di Malaysia. Variabel board size berpengaruh posistif signifikan terhadap carbon emission disclosure di Malaysia, namun tidak berpengaruh di Indonesia serta terdapat perbedaan yang siginifikan antara kualitas pengungkapan emisi karbon baik di Indonesia maupun di Malaysia.